Innovation in formation and new image of the teacher - Popey-ool, Saida K. (The New Research of Tuva, 2011)
The reference to pedagogical image as an innovative educational gives the chance to create a stimulus for a faculty self-development, to strengthen its self-esteem (if it is restrained) both in own opinion, and in that of colleagues and students.